Plant Diversity in Various Agroforestry System Based on Cocoa in Pasaman, West Sumatra - Sumilia, Sumilia; Akhir, Nasrez; Syarif, Zulfadhly (International Journal of Environment, Agriculture and Biotechnology, 2019)
In Sumatra, cocoa has been cultivated by small holders in diverse agroforestry systems. But recently, companion shade trees are being removed in hopes of reaching higher cocoa yield. This study tests a hypothesis, that high cocoa productivity is compatible with shade and diversity if farmers apply good cocoa management. The study was conducted throughout 2018 in Sontang village, Pasaman district, West Sumatra. We aimed to compare cocoa yield, tree diversity, and ethnobotanical value in 3 shade management systems (low/medium/high). Twelve 20 x 20 m plots were sampled random lyunder each shade, resulting in 36 plots covering 1.44 ha. Plant diversity was measured by species inventories and usefulness was determined based on ethnobotanical interviews. The medium shade also showed the highest crop diversity and highest usefulness. The study concludes that the medium shade harbors suitable level of tree diversity with a positive impact on cocoa yield. We recommend training farmers in cocoa management while sustaining medium shade as a productive, useful and bio diverse system.